Analysis of the structure of medical reports concerning hearing loss due to exposure to noise as an occupational disease in Poland in the years 2017-2018 - Ireneusz Drożak; Elżbieta Pachucka-Włas; Anna Nowosad-Sugier; Paulina Drożak; Martyna Drożak (Kazimierz Wielki University, 2021)
Introduction and purpose. Hearing impairment caused by noise is defined as a symmetrical, slowly progressing, permanent, receiving loss of hearing, of cochlear or sensoneurinal type, which concerns especially high frequencies. Hearing loss develops within the space of many years of exposure to high levels of noise which causes it to be an occupational disease of those who work in such conditions for a long period of time. The aim of this work was to analyse the structure of medical reports concerning hearing loss as an occupational disease in Poland in the years 2017-2018. Material and method. An analysis concerned cases of diagnosis of hearing loss diagnosed as an occupational disease based on Centralny Rejestr Chorób Zawodowych Instytutu Medycyny Pracy. Results. The occurrence of cases of hearing loss due to occupational factors decreased in 2017 and 2018 compared to 2016. Almost all cases of hearing loss as an occupational disease concerned male workers. This problem is almost non-existent among female workers. Hearing loss was the most prevalent among workers at pre-retirement age and those who worked more than 20 years in exposure to noise. Compared to other occupational diseases, hearing loss is not common in Poland. Conclusions. A decrease in cases of hearing loss as an occupational disease suggests that a system of periodic examination which is 1 examination each year during first 3 years of employment with medical appointment and a reminder of hearing protection works very well. Actions taken by all services (doctors, nurses, Occupational Health and Safety inspectors and employers) responsible for the protection of a worker cause a proper downward trend of diagnoses of hearing loss as an occupational disease among employees in Poland.